The Role of Customer Satisfaction in Mediating the Influence of Service Quality on Repurchase Intention: (Study on Online Customers of Bali Travel Agent Panca Hanasta Tours in Bali) - Damar Giri Priyanto; Komang Agus Satria Pramudana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Tourism activities in Indonesia are activities that can make a big contribution to the country. One form of contribution to increasing tourism is the activity of Online Travel Agents. Bali Panca Hanasta Tours is one of the Online Travel Agents in Bali that prioritizes the quality of service to encourage consumer repurchase intentions. The quality of service presented is expected to be able to provide a sense of satisfaction to customers by paying attention to customer needs and desires in order to be able to increase consumer repurchase intentions for the services provided. This study aims to understand the effect of service quality on repurchase intentions and the role of customer satisfaction as a mediating variable on online travel agent customers of Bali Panca Hanasta Tours in Bali. This study involved 100 respondents of Bali Panca Hanasta Tours customers. The data collection method was carried out through an online questionnaire, and data analysis using path analysis. The results of this study indicate that service quality has a positive and significant effect on repurchase intentions, and customer satisfaction successfully partially mediates the effect of service quality on repurchase intentions. The implications of the results of this study theoretically can be a reference for other researchers who want to study service quality, customer satisfaction, and repurchase intentions. In practice, it is expected to be a consideration and input for marketers and business actors in maximizing service quality and customer satisfaction as an effective and sustainable marketing strategy to increase repurchase intentions.